Nanoenviroments of the β-Subunit of L-Type Voltage-Gated Calcium Channels in Adult Cardiomyocytes - Cruz-Garcia, Yiliam; Barkovits, Katalin; Kohlhaas, Michael; Pickel, Simone; Gulentz, Michelle; Heindl, Cornelia; Pfeiffer, Kathy; Eder-Negrin, Petra; Maack, Christoph; Marcus, Katrin; Kuhn, Michaela; Miranda-Laferte, Erick (Frontiers in Cell and Developmental Biology, 2022)
In cardiomyocytes, Ca2+ influx through L-type voltage-gated calcium channels (LTCCs) following membrane depolarization regulates crucial Ca2+-dependent processes including duration and amplitude of the action potentials and excitation-contraction coupling. LTCCs are heteromultimeric proteins composed of the Cavα1, Cavβ, Cavα2δ and Cavγ subunits. Here, using ascorbate peroxidase (APEX2)-mediated proximity labeling and quantitative proteomics, we identified 61 proteins in the nano-environments of Cavβ2 in cardiomyocytes. These proteins are involved in diverse cellular functions such as cellular trafficking, muscular contraction, sarcomere organization and excitation-contraction coupling. Moreover, pull-down assays and co-immunoprecipitation analyses revealed that Cavβ2 interacts with the ryanodine receptor 2 (RyR2) in adult cardiomyocytes, probably coupling LTCCs and the RyR2 into a supramolecular complex at the dyads. This interaction is mediated by the Src-homology 3 domain of Cavβ2 and is necessary for an effective pacing frequency‐dependent increase of the Ca2+-induced Ca2+ release mechanism in cardiomyocytes.